Penerapan Metode Resitasi Terhadap Hasil Belajar Fisika pada Materi Usaha dan Pesawat Sederhana Kelas VIII SMP Negeri 1 Lawe Bulan Kutacane Tahun Ajaran 2023/2024 - Hartono, Makmur (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to examine the impact of the Recitation method on the learning outcomes in Physics, specifically on the topics of Work and Simple Machines, among eighth-grade students at SMP Negeri 1 Lawe Bulan during the 2023/2024 academic year. The research was conducted using a quasi-experimental method with a one-group pretest-posttest design and a saturated sampling technique to select a sample of 20 students. A multiple-choice test was employed as the instrument to measure students' learning outcomes. Data were analyzed using a one-sample t-test to compare the average student learning outcomes against the school’s minimum competency criteria (KKM). The analysis revealed a t-value (t_hitung) of 3.4, which exceeds the critical value (t_tabel) of 2.086 at a 0.05 significance level, indicating a significant effect of the Recitation method on students' Physics learning outcomes. In conclusion, the Recitation method is effective in enhancing students' learning outcomes in the studied topics.